Business Intelligence Solutions for Enhanced Accounting Decision-Making in Digital Transformation - Jones, Vivien Amara (The Indonesian Institute of Science and Technology Research, 2024)
In the era of fast-growing digital transformation, integrating business intelligence (BI) solutions in accounting decision-making has become essential for companies. This research reviews the critical role of BI solutions in optimizing the accounting decision-making process amid digital transformation. The method used in this research is a descriptive method with a qualitative approach, while the data used is secondary data obtained from previous studies. The data was collected through literature study techniques and analyzed qualitatively. The results of this study show that Business Intelligence (BI) plays a vital role in optimizing financial data presentation, adaptability to business changes, and providing competitive advantage through informed decision-making, especially in today's digital era. Implementing BI in an economic environment can improve efficiency, provide deep insights, and strengthen a company's competitiveness. BI is a technology tool and a strategic foundation supporting a company's success in the ever-changing digital era through its adaptability and ability to process data for decision-making.